How Does Consumer Experience with Cosmetics Products Create EWOM, Satisfaction, and Loyalty? - Fatmawati, Indah; Amanati, Annisa Khoirul (Jurnal Manajemen Bisnis, 2023)
Research aims: This study investigates how consumer experience with local beauty products influences Electronic Word of Mouth (EWOM), satisfaction, and loyalty.Design/Methodology/Approach: The researchers employed a quantitative approach with an explanatory survey design. The setting was a local medium, low-end beauty product in Indonesia that competes with many global brands. The respondents were 160 women who recently purchased, used the brand, and performed EWOM. The researchers used online questionnaires to collect data distributed via Google forms. The proposed hypotheses were then tested using Structural Equation Modeling (SEM) with the AMOS version 22.0 application. Research findings: This study found that (1) experiential marketing had a positive impact on customer satisfaction, EWOM, and customer loyalty; (2) customer satisfaction and EWOM also positively impacted customer loyalty; (3) while customer satisfaction mediated the effect of experiential marketing on customer loyalty, (4) EWOM mediated the experiential marketing effect on customer loyalty.Theoretical contribution/Originality: This study improved people’s understanding of the importance of creating costumers experience, which contributed to their satisfaction and willingness to perform EWOM, despite its direct influence on customer loyalty. This study also gives insight into customer satisfaction and willingness to perform EWOM, which will shape their loyalty to the product. The researchers further highlight the existence of customer satisfaction and EWOM in forming customer loyalty since those two constructs significantly mediate the relationship between experiential marketing and customer loyalty.Practitioner/Policy implication: The marketer needs to create a good customer experience, shaping customers’ satisfaction and influencing them to perform Electronic Word of Mouth. Furthermore, satisfied customers and those who already make an EWOM will create customer loyalty.Research limitation/Implication: The researchers identified three limitations and proposed suggestions for future study. First, the researchers used limited respondents, which may influence the generalization of this research’s findings. Increasing the sample size may improve the research findings' generalizability. Second, most respondents' backgrounds were also limited to university students, while getting more varied respondents may give different results. Finally, since the researchers only considered four variables in this research model, the researchers proposed that future research should consider additional variables to explain this phenomenon better.